A bilayer conducting polymer structure for planar perovskite solar cells with over 1,400 hours operational stability at elevated temperatures - Zhao, Yicheng; Heumueller, Thomas; Zhang, Jiyun; Luo, Junsheng; Kasian, Olga; Langner, Stefan; Kupfer, Christian; Liu, Bowen; Zhong, Yu; Elia, Jack; Osvet, Andres; Wu, Jianchang; et al. (Nature Energy, 2021)
The long-term stability of perovskite solar cells remains a challenge. Both the perovskite layer and the device architecture need to endure long-term operation. Here we first use a self-constructed high-throughput screening platform to find perovskite compositions stable under heat and light. Then, we use the most stable perovskite composition to investigate the stability of contact layers in solar cells. We report on the thermal degradation mechanism of transition metal oxide contact (for example, Ta-WOx/NiOx) and propose a bilayer structure consisting of acid-doped polymer stacked on dopant-free polymer as an alternative. The dopant-free polymer provides an acid barrier between the perovskite and the acid-doped polymer. The bilayer structure exhibits stable ohmic contact at elevated temperatures and buffers iodine vapours. The unencapsulated device based on the bilayer contact (with a MgF2 capping layer) retains 99% of its peak efficiency after 1,450 h of continuous operation at 65 degrees C in a N-2 atmosphere under metal-halide lamps. The device also shows negligible hysteresis during the entire ageing period.
CRIS-Team WoS Importer:2021-12-24

Advances in Lead-Free Perovskite Single Crystals: Fundamentals and Applications - Tailor, Naveen Kumar; Kar, Shaoni; Mishra, Pranjal; These, Albert; Kupfer, Christian; Hu, Hanlin; Awais, Muhammad; Saidaminov, Makhsud; Dar, M. Ibrahim; Brabec, Christoph; Satapathi, Soumitra (ACS Materials Letters, 2021)
With rapid progress in the deployment of metal halide perovskites in various device applications such as solar cells, light-emitting devices, field-effect transistors, photodetectors, etc., the next eminent focus is on the single crystals of these materials. With a lack of grain boundaries and low trap densities, remarkably long charge carrier diffusion lengths, and high ambient and operational stabilities, this class of materials seems greatly promising. Yet, the growing concern for lead toxicity in commercial semiconductor devices has entailed a thrust in the research of alternative lead-free perovskites, including their single crystalline forms. However, there is still no consolidated account of the state-of-the-art in this domain and accordingly, countless feasible systems still remain unexplored. To bridge this gap, we attempt to provide here, an up-to-date overview of lead-free perovskite single crystals with respect to their synthesis methods, structural diversity, stability, photophysical and electrical properties, and device applications. We discuss various approaches to designing, modeling, fabricating, and characterizing new single-crystal systems and conclude with some critical insights for further investigating this field of research.
CRIS-Team Scopus Importer:2021-07-16

Closing the loop: recycling of MAPbI3 perovskite solar cells - Wu, Zhenni; Sytnyk, Mykhailo; Zhang, Jiyun; Babayeva, Gülüsüm; Kupfer, Christian; Hu, Jin; Arnold, Simon; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Energy and Environmental Science, 2024)
Closed-loop recycling is crucial in the rapidly expanding era of photovoltaic deployment. Yet, the recycling of commercial silicon photovoltaic modules presents challenges due to laborious component separation. In contrast, layers in solution-processed solar cells can be separated with relative ease through selective dissolution. In this study, we report on the recovery of every layer in a planar MAPbI3 perovskite solar cell using a layer-by-layer solvent extraction approach, followed by purification or modification to restore quality. This method potentially allows for up to 99.97% recycled mass, thereby conserving resources and reducing waste. We assessed material quality by substituting each fresh material with its recycled equivalent during solar cell production. Subsequently, solar cells were fabricated with either several or all layers comprising recycled materials. Every combination yielded efficiency comparable to cells constructed exclusively with fresh materials, demonstrating the efficacy of the developed recycling process. Our mass and value analysis highlights ITO glass has the highest recycling priority and the need for circular utilization for by-product chemicals, especially cleaning agents. Techno-economic projections suggest that the proposed recycling procedure has the potential to afford substantial cost savings. In the lab, recycling could reduce material costs by up to 63.7%, in industrial manufacturing by up to 61.4%. A life cycle assessment reveals this recycling method can reduce environmental impacts.
CRIS-Team Scopus Importer:2024-06-07

Cs2AgxNa1-xBiyIn1-yCl6 perovskites approaching photoluminescence quantum yields of 100% - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasia; Kupfer, Christian; Osvet, Andres; Dzhagan, Volodymyr; Zahn, Dietrich R. T.; Hauch, Jens; Brabec, Christoph J. (Materials Advances, 2022)
A new single-step and green approach for the synthesis of microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 (CANBIC) perovskites in ambient conditions is introduced. The CANBIC powders emit broadband self-trapped excitonic photoluminescence (PL) with a champion PL quantum yield (QY) of 98 +/- 2% and a PL lifetime of ca. 2 mu s observed for x = 0.40 and y = 0.01-0.02. The study focuses on the dependence of structural, spectral, and photophysical properties of CANBICs on Bi content. CANBICs are solid solutions with isomorphous In-to-Bi substitution with the bandgap and valence band edge energy decreasing gradually with increasing y. The PL QY and the rate constant of the radiative recombination showed volcano-shaped dependences on the Bi content, while the rate of the non-radiative recombination revealed a drastic growth by three orders of magnitude as the Bi fraction y was elevated from 0.01 to 1.0 indicating that BiCl6 units are responsible for non-radiative recombination.
CRIS-Team WoS Importer:2022-09-09

Highly Luminescent Transparent Cs2AgxNa1-xBiyIn1-yCl6 Perovskite Films Produced by Single-Source Vacuum Deposition - Stroyuk, Oleksandr; Raievska, Oleksandra; Sebastia-Luna, Paz; Huisman, Bas A.H.; Kupfer, Christian; Barabash, Anastasia; Hauch, Jens; Bolink, Henk J.; Brabec, Christoph J. (ACS Materials Letters, 2023)
Thermal deposition of halide perovskites as a universal and scalable route to transparent thin films becomes highly challenging in the case of lead-free double perovskites, requiring the evaporation dynamics of multiple metal halide sources to be balanced or a single-phase precursor preliminary synthesized to achieve a reliable control over the composition and the phase of the final films. In the present Letter, the feasibility of the single-source vacuum deposition of microcrystalline Cs2AgxNa1-xBiyIn1-yCl6 double perovskites into corresponding transparent nanocrystalline films while preserving the bulk spectral and structural properties is shown. The perovskite films produced from the most emissive powders with x = 0.40 and y = 0.01 revealed a photoluminescence quantum yield of 85%, highlighting thermal evaporation as a promising approach to functional perovskite-based optical materials.
CRIS-Team Scopus Importer:2023-02-03

High-Throughput Robotic Synthesis and Photoluminescence Characterization of Aqueous Multinary Copper–Silver Indium Chalcogenide Quantum Dots - Stroyuk, Oleksandr; Raievska, Oleksandra; Langner, Stefan; Kupfer, Christian; Barabash, Anastasia; Solonenko, Dmytro; Azhniuk, Yuriy; Hauch, Jens; Osvet, Andres; Batentschuk, Miroslaw; Zahn, Dietrich R. T.; Brabec, Christoph (Particle & Particle Systems Characterization, 2021)
The feasibility of a high-throughput robot-assisted synthesis of complex Cu1-xAgxInSySe1-x (CAISSe) quantum dots (QDs) by spontaneous alloying of aqueous glutathione-capped Ag–In–S, Cu–In–S, Ag–In–Se, and Cu–In–Se QDs is demonstrated. Both colloidal and thin-film core CAISSe and core/shell CAISSe/ZnS QDs are produced and studied by high-throughput semiautomated photoluminescence (PL) spectroscopy. The silver-copper-mixed QDs reveal clear evidence of a band bowing effect in the PL spectra and higher average PL lifetimes compared to the counterparts containing silver or copper only. The photophysical analysis of CAISSe and CAISSe/ZnS QDs indicates a composition-dependent character of the nonradiative recombination in QDs. The rate of this process is found to be lower for mixed copper-silver-based QDs compared to Cu- or Ag-only QDs. The combination of the band bowing effect and the suppressed nonradiative recombination of CAISSe QDs is beneficial for their applications in photovoltaics and photochemistry. The synergy of high-throughput robotic synthesis and a high-throughput characterization in this study is expected to grow into a self-learning synthetic platform for the production of metal chalcogenide QDs for light-harvesting, light-sensing, and light-emitting applications.
CRIS-Team Scopus Importer:2021-09-10
Keywords: combinatorial synthesis; semiconductor nanocrystals; spontaneous alloying; ternary chalcogenides; time-resolved photoluminescence

High-Throughput Time-Resolved Photoluminescence Study of Composition- And Size-Selected Aqueous Ag-In-S Quantum Dots - Stroyuk, Oleksandr; Raievska, Oleksandra; Kupfer, Christian; Solonenko, Dmytro; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph; Zahn, Dietrich R.T. (Journal of Physical Chemistry C, 2021)
Brightly luminescent, composition- and size-selected aqueous Ag-In-S (AIS) and Zn-diffused core/shell AIS/ZnS (ZAIS) quantum dots (QDs) were studied by high-throughput time-resolved photoluminescence (TRPL). Both QD size and QD composition effects on the photophysical properties of AIS (ZAIS) were probed independently by using an automated high-throughput TRPL setup. Linear relationships were found between the average PL lifetimes of AIS and ZAIS QDs and their respective bandgaps (Eg) indicating that the dynamics of the radiative recombination is governed mostly by the energy of the QD excited state irrespective of which factor is varied affecting the QD bandgap, i.e., their size or composition. The rate constants of radiative and nonradiative recombination were evaluated as a function of Eg forming continuous dependences for the entire AIS and ZAIS QD families. The rate of nonradiative recombination increases steeply for smaller QDs with Eg > 2.2 eV for both core AIS and core/shell ZAIS QDs, indicating that the interfacial electron transfer is the major contributor to the observed dependence. A strong decrease of the PL lifetime of AIS (and ZAIS) QDs in dense QD films or QDs incorporated into polyvinylpyrrolidone films was observed as compared to colloidal solutions. A reversible character of this effect upon polymer film dissolution shows that such behavior originates from energy (or electron) transfers among the QDs brought into close contact in the films. This phenomenon is expected to be of significance for the application of ternary QDs as a light-harvesting material.
CRIS-Team Scopus Importer:2021-07-02

Intercalating-Organic-Cation-Induced Stability Bowing in Quasi-2D Metal-Halide Perovskites - Zhang, Jiyun; Langner, Stefan; Wu, Jianchang; Kupfer, Christian; Lüer, Larry; Meng, Wei; Zhao, Baolin; Liu, Chao; Daum, Manuel; Osvet, Andres; Li, Ning; Halik, Marcus; et al. (ACS Energy Letters, 2022)
Quasi-2D metal-halide perovskites with Ruddlesden-Popper structures have shown promising stability due to the protective effects of the intercalating organic cations. However, a systematic study of the effect of intercalating organic cations on stability has rarely been reported. Here we use a high-throughput-robot platform to fabricate over 300 perovskite films and study the effect of cations and their concentrations on the thermal stability of perovskite films. We find that approximately 20-25 mol % of intercalating organic cations into MAPbI3 (nominal n = 4/5) can maximize the film stability, while higher/lower concentrations lead to inferior stability, which is termed stability bowing in analogy to band-gap bowing. A model with two competitive effects of the intercalating organic cation (better protection vs more defects) is proposed to rationalize this behavior. We anticipate this work to provide new insights into the stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-02-11

Mechanochemical Synthesis of Cesium Titanium Halide Perovskites Cs2TiBr6-xIx (x=0, 2, 4, 6) - Kupfer, Christian; Elia, Jack; Kato, Masashi; Osvet, Andres; Brabec, Christoph (Crystal Research and Technology, 2022)
Perovskite materials have a great variety of applications, such as X-ray detection, lasing and piezoelectric, or solar energy harvesting. While achieving record efficiencies, perovskite solar cells suffer from the presence of toxic lead in their crystal structure. One possibility to circumvent this issue is via the family of vacancy-ordered double-perovskites, where lead atoms are replaced alternatingly by a tetravalent atom and a vacant lattice site. From this material family, Cs2TiBr6 has recently emerged as a promising candidate due to its favorable reported properties for photovoltaic applications specifically. This paper presents a novel and facile synthesis route to obtain phase-pure Cs2TiBr6 and its lesser-studied iodine-based relatives Cs2TiBr4I2, Cs2TiBr2I4, and Cs2TiI6 via high-energy mechanochemical ball milling. The materials are characterized with structural, microscopic, and photophysical techniques to reveal indirect bandgaps with values of 1.88, 1.13, 1.04, and 1.02 eV but also a distinct lack of any significant photoluminescence (PL) and a high instability under ambient conditions. These findings enable us to clarify the previously controversial properties of Cs2TiBr6 and establish its role in the vast landscape of perovskite photovoltaics.
CRIS-Team WoS Importer:2022-11-25
Keywords: ball milling; cesium titanium halides; lead-free; stability

Spontaneous alloying of ultrasmall non-stoichiometric Ag-In-S and Cu-In-S quantum dots in aqueous colloidal solutions - Stroyuk, Oleksandr; Raievska, Oleksandra; Solonenko, Dmytro; Kupfer, Christian; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph; Zahn, Dietrich R. T. (RSC Advances, 2021)
The effect of spontaneous alloying of non-stoichiometric aqueous Ag-In-S (AIS) and Cu-In-S (CIS) quantum dots (QDs) stabilized by surface glutathione (GSH) complexes was observed spectroscopically due to the phenomenon of band bowing typical for the solid-solution Cu(Ag)-In-S (CAIS) QDs. The alloying was found to occur even at room temperature and can be accelerated by a thermal treatment of colloidal mixtures at around 90 °C with no appreciable differences in the average size observed between alloyed and original individual QDs. An equilibrium between QDs and molecular and clustered metal-GSH complexes, which can serve as “building material” for the new mixed CAIS QDs, during the spontaneous alloying is assumed to be responsible for this behavior of GSH-capped ternary QDs. The alloying effect is expected to be of a general character for different In-based ternary chalcogenides.
CRIS-Team Scopus Importer:2021-07-23

Unravelling material properties of halide perovskites by combined microwave photoconductivity and time-resolved photoluminescence spectroscopy - Kupfer, Christian; Le Corre, Vincent Marc; Li, Chaohui; Lüer, Larry; Forberich, Karen; Kato, Masashi; Osvet, Andres; Brabec, Christoph (Journal of Materials Chemistry C, 2024)
To take advantage of the huge compositional space of metal halide perovskites, a reliable and fast characterization method is required. By combining time-resolved photoluminescence (trPL) with microwave photoconductivity measurements, we are able to rapidly extract fundamental material properties of promising perovskite materials from bare films. This is achieved by incorporating a rate-equation model into a fitting algorithm based on Bayesian optimization to globally fit the experimental results. Including microwave photoconductivity measurements into our analysis significantly enhances the accuracy of estimating recombination rate constants. Additionally, it grants us the ability to determine the ratio of electron and hole mobilities, a crucial charge transport property that cannot be obtained solely through time-resolved photoluminescence measurements. Furthermore, the high sensitivity of microwave photoconductivity measurements to long-lived trap states yields information about the trap-assisted recombination, which is a major source of efficiency loss for solar devices and is difficult to assess from pure trPL measurements. In this work, we introduce the fundamental principles of microwave photoconductivity, along with the employed rate-equation model and fitting techniques. We then outline the procedure for conducting measurements and extracting the recombination rate constants, trap density, and mobility ratio. Subsequently, we highlight the benefits of combining both methods through a comparison of results from fits using only trPL with those from fits incorporating combined signals on a simulated dataset. We also discuss the merits of conducting intensity-dependent measurements. Finally, we present the annealing-dependent results obtained from a highly relevant triple-cation, mixed-halide perovskite, FA0.82MA0.13Cs0.05Pb(I0.87Br0.13)3, as an application example, where we uncover the presence of long-lived traps beyond 10 μs.
Created from Fastlane, Scopus look-up